Transparency of Regional Budget and Expenditure (APBD) through the Optimization of E-Budgeting Implementation - Tanjung, Sawaluddin F; Junaidi, Junaidi; Zulgani, Zulgani; Assegaf, Setiawan (Nomico, 2024)
The implementation of budgetary reform in local government budgeting is often viewed as lacking a structured system. This is marked by low transparency and accountability in the management of local budgets. Financial management systems that contradict the principles of good governance necessitate transparency and accountability in all areas of government. The advent of e-budgeting is evidence of the utilization of e-government programs in Indonesia. E-budgeting is expected to be a solution for enhancing transparency and accountability in local budget management. With e-budgeting, the public can more easily access information about budget allocations and their usage. Public participation is also anticipated to increase, allowing for more effective oversight of local government budgets. This transparency not only supports the improvement of financial management at the local level but also contributes to the enhancement of public service quality. Therefore, the implementation of e-budgeting is expected to strengthen good governance and increase public trust in local governments. Active public participation and high transparency are key to realizing a more efficient and accountable local budget management system.